Menopausal transitional and postmenopausal women’s voices: “what influences their adherence to self-management”: a systematic review and meta-synthesis of qualitative studies - Jiang, Yan; Tao, Minfang; Huang, Cuiqin; Lu, Qunfeng (Frontiers in Public Health, 2025)
BackgroundSelf-management plays a vital role in preventing the occurrence of severe menopausal symptoms and hazards. There has been a lack of systematic reviews exploring the influencing factors and challenges faced by menopausal transitional and postmenopausal women regarding their self-management experiences and perceptions.ObjectiveThis study aimed to synthesize the self-management experiences, motivations, and challenges of menopausal transitional and postmenopausal women, to inform the design and development of self-management programs. The results were analyzed according to the capability, opportunity, and motivation model of behavior (COM-B) model, and suggestions for improvement were subsequently put forward.MethodsA meta-aggregation method was used to synthesize qualitative studies. Ten databases were searched for studies published up to 3 April 2025. Two researchers assessed the quality and risk of bias and extracted data from the included studies independently. A thematic synthesis approach was used to analyze the key findings using the COM-B model.ResultsA total of 23 primary studies containing 808 participants were included. Six themes with fifteen sub-themes were recognized after reading and coding of the articles: Poor cognition (misconceptions about menopause and treatment, insufficient knowledge, lack of active health literacy, and lack of empowerment); physical restriction (medical conditions and fatigue); restricted environment (limited resources and restrictions on amenities); impact of interpersonal circle (the influence of family support and understanding, social belonging, and lack of useful advice from experts); planning and adherence (setting a solid plan and the psycho-immune system); and expectations for keeping health (perceived health benefits and health crisis concern). Analysis of the findings according to the COM-B model revealed that poor cognition, physical restriction, and restricted environment are the challenges faced by menopausal transitional and postmenopausal women. Expectations for keeping healthy serve as the motivation for self-management behaviors. Impact of the interpersonal circle, planning, and adherence are the important influencing factors in maintaining self-management behavior in menopausal transitional and postmenopausal women.ConclusionThis study shows that knowledge, empowerment, and family and social support are key motivators for self-management among perimenopausal and postmenopausal women. We believe that addressing perimenopausal and postmenopausal women’s knowledge needs, improving their knowledge, empowering the skills of healthcare providers, and reinforcing the supportive environment for self-management behaviors, including physical activity, access to community health services, and a supportive interpersonal environment, are effective interventions to promote self-management.Systematic review registrationThe protocol for this study has been registered with PROSPERO(Registration Number: CRD420251025120). https://www.crd.york.ac.uk/PROSPERO/view/CRD420251025120.